2022
DOI: 10.1177/00219983221121870
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and assessment of nanocomposites based on natural rubber latex reinforced with multiwall carbon nanotubes for Gamma rays shielding applications

Abstract: Reinforcement of the flexible shielding properties of natural rubber (NRL) was achieved through various content Multi-walled carbon nanotubes (MWCNTs) prepared from a simple solution using mixing method. We reported the structure change of NRL upon addaing different contenets of MWCNTs. The results from the X-ray diffraction, Scanning electron microscopy and Fourier-transform infrared spectroscopy revealed that the nanocomposites have been successfully prepared, making them fitting to impact significant improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Studies have shown that the material possess EMI shielding effectiveness of 59 dB at maximum composition of CNTs (Muringayil Joseph et al, 2022). Figure 8 shows diagrammatic representation of the EMI shielding efficiency of SBR-MWCNT composites (Abdeldaym and Elhady, 2022). Single-walled carbon nanotubes as fillers can be introduced to fluorinated rubber and the material exhibits electromagnetic interference (EMI) shielding.…”
Section: Emi Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the material possess EMI shielding effectiveness of 59 dB at maximum composition of CNTs (Muringayil Joseph et al, 2022). Figure 8 shows diagrammatic representation of the EMI shielding efficiency of SBR-MWCNT composites (Abdeldaym and Elhady, 2022). Single-walled carbon nanotubes as fillers can be introduced to fluorinated rubber and the material exhibits electromagnetic interference (EMI) shielding.…”
Section: Emi Shieldingmentioning
confidence: 99%
“…Abdeldaym et al investigated the Gamma rays shielding applications of natural rubber latex reinforced with multiwall carbon nanotubes. From the values of linear attenuation coefficients (L) and half-value thickness for NRL/MWCNTs nanocomposite it was concluded that the fabricated material offers promising radiation-shielding properties (Abdeldaym and Elhady, 2022). Several elastomeric polymers -CNT composites were developed to make them a potential candidate for EMI shielding applications as listed in Table 2.…”
Section: Emi Shieldingmentioning
confidence: 99%
“…Moreover, its thermal history depends on the measurement method and the rate of heating or cooling, as well as on many other factors, including the use of various processing aids, such as plasticizers and nanofillers. 22,23 However, the most frequently used modifiers of PVC glass transition temperature are specific plasticizers, in the form of small molecules, which are introduced into a polymer macromolecular structure and usually lead to a reduction in the Tg value. 24 Despite a large number of sources [25][26][27] that report on the impact of nanoadditives on the properties of PVC nanocomposites, only some of them concern the influence of nanofillers on the thermal properties of this polymer in its glassy state.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, gamma radiation has been used in order to test the shielding capability of natural polymers. Cotton fabric coated with different materials such as barite (barium sulphate) [56,57], raw jute or composites made with jute [58][59][60], natural rubber with carbon nanotube additions [61] possess the ability to shield gamma radiation. Rare-earth-doped rubber can attenuate cosmic rays by up to 10% compared with conventional aluminum shielding [62].…”
Section: Introductionmentioning
confidence: 99%